The effects of carbohydrate-restricted diets on 24-h mean blood glucose levels measured by continuous glucose monitoring in type 2 diabetes: a hypothesis-generating meta-analysis - Wang, Chou; Pei, Aizhen (Frontiers in Nutrition, 2025)
PurposeTo conduct a hypothesis-generating meta-analysis exploring trends in 24-h mean blood glucose via CGM in T2DM patients on carbohydrate-restricted diets (CRDs), to inform future trial design and intervention duration.MethodsThis study applied predefined inclusion and exclusion criteria and systematically searched five major databases—PubMed, Web of Science, Embase, Cochrane Library, and EBSCOhost—from their inception to May 16, 2025. The methodological quality of the selected studies was assessed in accordance with the Cochrane Handbook (version 5.1). Statistical analyses, including effect size estimation and sensitivity testing, were conducted using STATA version 18. Bias evaluation was performed using Review Manager version 5.4. Exploratory trend analyses were carried out using Microsoft Excel 2019.ResultsA total of 1,322 articles were retrieved, and after four rounds of screening, seven studies involving 301 participants (mean age 58.1 ± 8.64 years) were included in the meta-analysis. Results showed that CRDs significantly improved 24-h mean blood glucose in patients with T2DM (d = −0.51, 95% CI: −0.88 to −0.14, p < 0.05), with exploratory trend analysis suggesting a positive correlation between intervention duration and the magnitude of 24-h mean blood glucose reduction.ConclusionCRDs may improve 24-h MBG in patients with T2DM, with exploratory trend analysis suggesting greater benefits with longer intervention durations. However, due to the limited number and relatively short duration of included studies, further high-quality randomized controlled trials with longer durations (≥1 year) are warranted to evaluate the differential effects of short-term and long-term CRDs on glycemic outcomes in patients with T2DM.Systematic review registrationCRD420251069702, https://www.crd.york.ac.uk/PROSPERO/.